2013
DOI: 10.1103/physrevlett.110.216403
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Metallicity in K-doped Picene: Importance of Electronic Correlations

Abstract: Potassium-doped picene (Kxpicene) has recently been reported to be a superconductor at x = 3 with critical temperatures up to 18 K. Here we study the electronic structure of K-doped picene films by photoelectron spectroscopy and ab initio density functional theory combined with dynamical mean-field theory (DFT+DMFT). Experimentally we observe that, except for spurious spectral weight due to the lack of a homogeneous chemical potential at low K-concentrations (x ≈ 1), the spectra always display a finite energy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 44 publications
(45 reference statements)
7
69
0
Order By: Relevance
“…In this context both many-body effects and electron-phonon interactions would be important [9,[14][15][16][37][38][39][40]. Finally, let us remind one that after the seminal work by Mitsuhashi et al [1] showing the existence of superconducting phases for potassium-intercalated picene, additional experimental evidence points to a metallic behavior of K 3 picene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context both many-body effects and electron-phonon interactions would be important [9,[14][15][16][37][38][39][40]. Finally, let us remind one that after the seminal work by Mitsuhashi et al [1] showing the existence of superconducting phases for potassium-intercalated picene, additional experimental evidence points to a metallic behavior of K 3 picene.…”
Section: Discussionmentioning
confidence: 99%
“…3 of Ref. [14]). Notice that our interaction model is similar to theirs (although we are coupling K and picene bands and our U value is sensibly larger), and therefore, our quarter-filled two-band model produces a spectral function that resembles the one shown at the top of the mentioned figure ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in the computed geometry of picene in K2Picene compared to solid picene is consistent with the occupation of the LUMO orbital when forming the dianion (Supplementary Figure 28). Density functional plus dynamical mean field theory (DFT+DMFT) calculations on KxPicene 39 suggest the opening of a Mott gap by electron correlation in both LUMO and LUMO+1 bands in a multi-orbital correlated model, 40 which is required to explain the insulating behaviour of Cs2Phenanthrene, 32 and such correlation effects, which are not captured at the level of theory used here, may also contribute to the gap in the picene dianion solid. Raman spectroscopy does identify differences in the electronic behaviour of the K2Pentacene and K2Picene: high-frequency Raman modes display significant broadening in K2Picene, implying electron-phonon coupling, which is not observed in K2Pentacene (see Supplementary Section 4).…”
Section: Electronic Structurementioning
confidence: 99%
“…1 and Table I). Interacting electron theories that have been constructed for the doped acenes and phenacenes [20][21][22] , however, still fail to explain the two crucial experimental observations completely. Taking the combined effects of the Hubbard U and nonzero ∆ L,L+1 into consideration, reference 20 has concluded that K 3 picene in the normal state is a Mott-Hubbard semiconductor, with a completely filled L-band and a 1 2 -filled L+1-band.…”
Section: Introductionmentioning
confidence: 99%